309 A REPORT OF SCHINZEL-GIEDION SYNDROME AND A REVIEW OF THE LITERATURE. Issue 1 (1st January 2007) - Lehman, A. M.; Patel, M. S.; Friedman, J. M.
Abstract : We report the forty-third case of Schinzel-Giedion syndrome in the English literature. In the antenatal period, a male fetus was found to have bilateral hydronephrosis. The family history was noncontributory. Polyhydramnios preceded premature delivery at 36 weeks, and the infant was found to be plethoric, edematous, and dysmorphic. In keeping with a diagnosis of Schinzel-Giedion syndrome, the fontanelles were large and widely apart down to the nasal bone; there was hypertelorism, a wide, broad forehead, midface hypoplasia, a short, upturned nose, macroglossia, and a short neck. Other anomalies included a complex cardiac defect, widened and dense long bone cortices, mild ventriculomegaly, and abnormal fundi. Investigations for metabolic conditions were negative, the karyotype was 46 X, Y, and testing for an infectious etiology was negative. Massive bilateral hydronephrosis secondary to UPJ obstruction progressed and contributed to multisystem organ failure, with death at 13 days of life. Schinzel-Giedion syndrome is thought likely to be an autosomal recessive condition for which the genetic locus has not yet been discovered. A novel, unknown metabolic process has been hypothesized as the pathogenic mechanism.